복합 재난을 위한 장갑형 로봇의 차체 설계 - 박상현; 김무림; 김영렬; 김도익; 김준식; 신동빈; 서진호 (한국로봇학회, 2018)
In this paper, a design for a vehicle body of an armored robot for complex disasters is described. The proposed design considers various requirements in complex disaster situations. Fire, explosion, and poisonous gas may occur simultaneously under those sites. Therefore, the armored robot needs a vehicle body that can protect people from falling objects, high temperature, and poisonous gas. In addition, it should provide intuitive control devices and realistic surrounding views to help the operator respond to emergent situations. To fulfill these requirements of the vehicle body, firstly, the frame was designed to withstand the impact of falling objects. Secondly, the positive pressure device and the cooling device were applied. Thirdly, a panoramic view was implemented that enables real-time observation of surroundings through a number of image sensors. Finally, the cockpit in the vehicle body was designed focused on the manipulability of the armored robot in disaster sites.